2021
DOI: 10.3390/nu13041268
|View full text |Cite
|
Sign up to set email alerts
|

Bioflavonoid Robinin from Astragalus falcatus Lam. Mildly Improves the Effect of Metothrexate in Rats with Adjuvant Arthritis

Abstract: Anti-inflammatory potential of orally administrated bioflavonoid-robinin, active sub-stance of original drug Flaroninum™ (FL), was investigated in the combination with methotrexate (MTX) and in monotherapy in rats suffering from adjuvant-induced arthritis (AA). Robinin (kaempferol-3-O-robinoside-7-O-rhamnoside) was isolated from the aerial parts of Astragalus falcatus Lam. The monotherapy with robinin was not efficient in alleviating symptoms of AA. The combination of MTX with robinin was similarly active as M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…A total of 115 flavonoids from O. falcata was found through the search of the relevant literature [ 18 , 19 , 23 , 27 , 43 , 47 ], and among them, 90 active compounds were screened out based on Lipinski’s Rule of five [ 48 ]. Myricetin and robinin were also taken into consideration due to their previously reported pharmacological effects [ 49 , 50 ] ( Table S1 ). In total, 92 active compounds were used for the evaluation of the target prediction.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 115 flavonoids from O. falcata was found through the search of the relevant literature [ 18 , 19 , 23 , 27 , 43 , 47 ], and among them, 90 active compounds were screened out based on Lipinski’s Rule of five [ 48 ]. Myricetin and robinin were also taken into consideration due to their previously reported pharmacological effects [ 49 , 50 ] ( Table S1 ). In total, 92 active compounds were used for the evaluation of the target prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvant arthritis in Lewis rats is a well-known and reliable model of RA. The main clinical manifestations of AA are paw swelling and the loss of body weight [ 41 , 42 ]. CA in monotherapy did not have a significant effect on hind paw swelling ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…I am pleased that 19 papers published in this Special Issue [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], present novel findings and adhere to the above-mentioned current trends. I personally consider the fact, that some papers in this issue also reported negative or only mild effects of the tested compounds to be very important as well.…”
mentioning
confidence: 84%
“…Data from animal studies have shown: (a) combinations of colonic metabolites of quercetin can have a more pronounced effect on arterial blood pressure in rats [ 19 ]; (b) the flavonol robinin only mildly improved the effect of methotrexate in an adjuvant-induced arthritis model in rats [ 24 ]; (c) the impact of a polyphenol-rich extract from Aronia melanocarpa (chokeberries) on liver collagen, matrix metalloproteinases, and their tissue inhibitors in rats chronically exposed to cadmium [ 15 ].…”
mentioning
confidence: 99%